2016
DOI: 10.21608/jpp.2016.45528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Different Sourses of Organic Fertilizers and Seaweed Extract on Growth and Essential Oil of Sweet Fennel (Foeniculum vulgare Mill.) Plants.

Abstract: This work was carried out during the two successive winter seasons of 2014/ 2015 and 2015/ 2016 at Meet Assas village, (Private Farm) Gharbieh Governorate, Egypt, on sweet fennel plants, to investigate the utilization of some different sources and rates of organic manure (chicken and farmyard manure) at 50 and100 % of recommended rate / fed., foliar fertilizer of seaweed extracts ( without and with 2 g / liter) compared with mineral NPK fertilizer at 50 and 100 % of recommended rate /fed., and their interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…Faridvand et al [25] reported that organic fertilizers improved the growth of fennel due to their effect on the availability of most of the micro and macronutrients compared to chemical fertilizers. Eisa [61] found that organic additives (farmyard and chicken manure) and mineral NPK (50 and 100% of RD) resulted in the highest N, P, and K content in fennel plants. Previous studies proved that the accumulation of N, P, and K in plants in response to chemical, organic, and bio-fertilizations as reported in caraway [47], chamomile [62], collard [63], moringa [32], kale [64], and coriander [65].…”
Section: Discussionmentioning
confidence: 99%
“…Faridvand et al [25] reported that organic fertilizers improved the growth of fennel due to their effect on the availability of most of the micro and macronutrients compared to chemical fertilizers. Eisa [61] found that organic additives (farmyard and chicken manure) and mineral NPK (50 and 100% of RD) resulted in the highest N, P, and K content in fennel plants. Previous studies proved that the accumulation of N, P, and K in plants in response to chemical, organic, and bio-fertilizations as reported in caraway [47], chamomile [62], collard [63], moringa [32], kale [64], and coriander [65].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shehata et al (2011) and Eisa (2016) found that the percentages of N, P and K in leaves of sweet fennel and celeriac plant were increased significantly with foliar application of seaweed extract. The highest respect values of macronutrients (N, P and K) might be attributed to organic and mineral elements constituents of seaweed extract.…”
Section: Macronutrients Total Content In Both Wheat and Peanut Cropsmentioning
confidence: 99%
“…The results showed in figure (6) and table (5) that the gene SIActin has an effective response to the effect of organic and phosphate fertilizer , whether alone or in combination, as the treatment gave 160 kg. D -1 of phosphate fertilizer, and the genotype Dollap had the highest genetic expression, which reached ( 9.849155 ) , followed by the treatment of 8 T. D -1 and genotype Hannan, which amounted to ( 9.189587 ) , while the comparison treatment and Local genotype gave the lowest gene expression and was( 0.143587 ).…”
Section: Effect Of Organic and Phosphate Fertilizers On Siactin Gene ...mentioning
confidence: 99%
“…This is due to its spread in folk medicine and its uses in various pharmaceutical preparations, as it contains an important essential oil at a rate of (3-6%) and includes a number of effective and active compounds, including (Anethole), (Limonene), (α-pinene), (Estragol) and ( Fenchone), which has the distinctive aroma of a fennel, and these compounds are used as a diuretic, carminative, and sedative [2][3][4] . fennel is also used as a treatment for upper respiratory tract infections due to its sedative effects on bronchitis and cough [5,6]. He pointed out [7] that the leaves of the fennel are used in the treatment of diarrhea and sexual weakness.…”
Section: Introductionmentioning
confidence: 99%